The Effect of Mind Mapping Learning Media on Learning Achievement in al-Naḥwu al-Waḋiḥ at Madrasah Tsanawiyah - Asrofin, Dian; Salma, Kunti Nadiyah; Putra, Wahyu Hanafi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The application of mind mapping in nahwu subjects using the skills of words, pictures, logic and awareness space in an exciting way will impact student learning outcomes. This study aims to determine; (1) Increased value from before the implementation of mind mapping learning media. (2) The application of mind map media in nahwu lessons for class IX students at Mts Al-Imam Sawoo (3) The results of learning achievement after implementing mind mapping media. This research is quantitative research with data collection techniques using questionnaires and documentation. While the data analysis through instrument validity test and instrument reliability test. The study results: 1) it is known that the average value of the nahwu Al wadhih subject of class IX A and IX B students is 72.44%. 2) in the application of mind mapping media in class IX nahwu lessons, the interaction between teachers and students is perfect; even students are more active in the process. 3) the learning outcomes of Nahwu students in grade IX using mind mapping media have increased, which initially had an average of 72.44% to 79.5%.